Building Mental Health Capacity in Schools: Early Lessons from a Canadian Initiative - Friesen, Sharon; MacGregor, Stephen; Sumara, Dennis; Turner, Jennifer; Mesner, Brenna (International Journal of Education Policy and Leadership, 2025)
This article examines the early implementation of a provincial initiative aimed at improving mental health supports in Canadian elementary and secondary schools. A content analysis of 60 proposals submitted by school jurisdictions uncovered the organizational and cultural strengths and challenges that influence the development of mental health initiatives. The analysis revealed three strengths: readiness for change, tailored mental health solutions, and strategic leadership. Five challenges also emerged: fragmented service delivery, an overreliance on external service providers, a lack of qualified staff, difficulties in forming authentic partnerships with families and communities, and impediments to establishing an effective organizational infrastructure. The findings highlight the complexity of embedding mental health initiatives in schools and the importance of sustained leadership, professional learning, and community collaboration for long-term integration.